Tumor Budding Grade Based on the ITBCC 2016 Criteria is Associated with Lymphovascular Invasion and Lymph Node Involvement in Invasive Breast Carcinoma - Nelzima, Maisyah; Asri, Aswiyanti; Tofrizal, Alimuddin; Hilbertina, Noza; Mulyani, Henny; Devianti, Loli; Fadila, Zurayya (FORIKES, 2026)
Invasive breast carcinoma is a malignant neoplasm with metastatic potential influenced by various histopathological parameters, including tumor budding (TB). TB has emerged as a potential indicator of tumor aggressiveness; however, differences in assessment criteria may affect its clinical relevance. This study aimed to evaluate the association between TB grade and lymphovascular invasion (LVI) as well as lymph node involvement in invasive breast carcinoma using three different assessment criteria. A cross-sectional study was conducted on 44 cases of invasive breast carcinoma that met the inclusion criteria. TB was assessed at the invasive front using the International Tumor Budding Consensus Conference (ITBCC) 2016 criteria, as well as the criteria proposed by Usta et al. and Manimaran et al. LVI and lymph node status were determined through histopathological examination. The associations between variables were analyzed using the chi-square test or Fisher’s exact test, as appropriate. Tumor budding grade based on one standardized assessment system demonstrated a significant association with both LVI and lymph node involvement. In contrast, the other two grading approaches did not show statistically significant associations. As conclusion, within the context of this study, the ITBCC 2016 criteria appear to be more representative in reflecting tumor invasive activity in invasive breast carcinoma. These findings support the potential role of tumor budding as an additional indicator of tumor aggressiveness and highlight the importance of standardizing its assessment method in invasive breast carcinoma.Keywords: invasive breast carcinoma; tumor budding; lymphovascular invasion; lymph node involvement